On the 85th Birthday Anniversary of the RAS Corresponding Member, Professor A. A. Tolstonogov - I.V. Bychkov; V.A. Dychta; A. L. Kazakov; N. I. Pogodaev; V. A. Shelekhov (Известия Иркутского государственного университета: Серия "Математика")
The paper is dedicated to the scientific and scientific-pedagogical activities of the professor, Corresponding Member of the Russian Academy of Sciences A. A. Tolstonogov, who turns 85 in March 2025.